Global change effects on coniferous forests and grasslands - Breymeyer, A.I (SCOPE report, 1996)
This volume critically assesses the present state of our knowledge, reviews extant forest and grasslands models, and develops foundations for the design of diagnostic and predictive models, as well as identifying plans for future research on ecosystem response to global change. Carbon flow and storage are emphasised, although the flow and storage of key nutrients such as nitrogen, sulphur and phosphorus are also considered when deemed necessary to understand changes in the carbon budget of coniferous forests and grasslands.